Variance in male lifetime reproductive success and estimation of the degree of polygyny in a primate - Dubuc, Constance (Oxford University Press, 2014)
The degree of polygyny is predicted to influence the strength of direct male–male competition, leading to a high variance in male lifetime reproductive success and to reproduction limited to the prime period of adulthood. Here, we explore the variance in male lifetime reproductive success and reproductive time in an anthropoid primate forming multimale–multifemale groups. Males of this species form dominance hierarchies, which are expected to skew reproduction toward few high-ranking males. At the same time, however, females mate with multiple males (polygynandry), which should limit the degree of polygyny. Using 20 years of genetic and demographic data, we calculated lifetime reproductive success for the free-ranging rhesus macaque (Macaca mulatta) population of Cayo Santiago for subjects that died naturally or reached senescence. Our results show that 1) male lifetime reproductive success was significantly skewed (range: 0–47 offspring; males reproducing below average: 62.8%; nonbreeders: 17.4%), 2) variance in male lifetime reproductive success was 5 times larger than in females, and 3) male lifetime reproductive success was more influenced by variation in fecundity (60%) than longevity (25%), suggesting that some direct male–male competition takes place. However, the opportunity for selection (i.e., standardized variance in male lifetime reproductive success) is low compared with that in other large mammal species characterized by a high degree of polygyny. Moreover, male reproductive life extended much beyond the prime period, showing that physical strength was not required to acquire mates. We conclude that rhesus macaques exhibit a moderate degree of polygyny and, therefore, low levels of direct male–male competition for fertile females, despite the fact that males form linear dominance hierarchies.